Responses in the abundance of generalist birds to environmental gradients: The rufous-collared sparrow (Zonotrichia capensis) in the southern Neotropics - Bellocq, Maria Isabel (2011)
Bird species are adapted to certain ranges of physical conditions and will respond to environmental heterogeneity depending on their ability to exploit a broad range of resources and their tolerance to new environmental conditions. We used the rufous-collared sparrow as a model to explore how the abundance of generalist passerine birds may vary along environmental gradients in the southern Neotropics. We analyzed variations in the abundance along 6 gradients expressing variations in climate, productivity, the proportion of native forest in the landscape, the proportion of vegetation types through the transition between regions, and the intensity of human activities (agriculture, urbanization). The rufous-collared sparrow was most abundant in seasonal and semi-arid climates. Thermal amplitude was the best climatic predictor of the species abundance at the large scale. Within regions where climatic conditions are relatively homogeneous, land use better predicted abundance patterns. The species responded positively to increasing primary productivity, agricultural intensity, and native forest degradation and conversion and negatively to increasing urbanization. The rufous-collared sparrow adapts successfully to new environments created by human activities such as agriculture, ranching, forestry, and urbanization. Some native species may be tolerant to certain types and intensity of human activities, and knowledge of how they respond to both natural and human-created environments may help efforts to anticipate the impact of human activities on native birds in a changing world.